The Pakistan Army 1966-71 - Shaukat Riza Major General (Retd.) (GHQ,Rawalpindi Army Education Press, 1990)
This books covers the army activities between the years of 1966 to 1971.
Include Annexure, Bibliography, Illustrations and Index.
Keywords: Pakistan. Army -- Pakistan, Military